PENERAPAN KONSEP KELAS LITERASI VISUAL TERHADAP KETERAMPILAN MENULIS DISKRIPSI ANAK TUNARUNGU KELAS IV DI SLB - Ria Sari, Elfrida (Jurnal Pendidikan Khusus, 2016)
ABSTRACT   Hearing impairment had impact to the hindrance of the children’s speaking development. The hindrance of the children’s speaking development caused complex development problem such as the low information accepted so it had impact to the low vocabulary possessed by the children, the children’s social interaction was disturbed, and the children’s emotion and intelligence skill were disturbed. Therefore, developing speaking skill should be implemented as early as possible. One of them developed writing description skill through the concept application of visual literacy class. The purpose of this research was to prove the influence of the concept application of visual literacy class toward writing description skill to hearing impairment children of class IV in SDLB-B Karya Mulia 1 Surabaya. This research used quantitative approach with pre-experiment kind, and one-group pretest-posttest. The subject in this research was hearing impairment children of class IV in SDLB-B Karya Mulia 1 Surabaya numbering 7 children. The data collection technique used test and documentation. The data analysis technique used statistic non parametric with Wilcoxon Match Pairs Test. The result of data analysis indicated that there was significant influence of the concept application of visual literacy class toward writing description skill to hearing impairment children of class IV in SDLB-B Karya Mulia 1 Surabaya.   Keywords: Concept of visual literacy class, writing description skill